New Global Learning Cultures: Interdisciplinarity through networked technologies - Cochrane, Thomas; Keegan, Helen (AoIR Selected Papers of Internet Research, 2012)
The context in which higher education institutions (HEIs) now operate is facing fundamental changes; HEIs are often said to be in a time of crisis, and new models of education are being explored both within and outside the academy. The rise of open educational resources and practices and alternative forms of accreditation are gaining recognition as learners and educators explore new ways of learning and connecting both within and outside the institution. Simultaneous to this rise in new learning cultures and paradigms, traditional disciplinary boundaries are themselves being challenged as networked technologies and changing social/cultural conditions are leading to further critique of traditional pedagogies, and increasing support for interdisciplinarity. In this paper, we explore emerging and converging technologies and disciplines through two higher education international collaboration scenarios. These two projects illustrate the potential of interdisciplinary communities of practice to nurture and support new pedagogical paradigms. We conclude by identifying five design principles for global interdisciplinary projects.